Taro Tourism Village Development Strategy as an Eco-Spiritual Destination, in Gianyar Regency- Bali - Arie Yudhistira, Putu Gde (Journal of Business on Hospitality and Tourism, 2021)
Taro Village is one of the villages located in Tegallalang District, Gianyar Regency, Bali Province. This village has various kinds of potential, especially natural potential that can be used as a tourist destination. In addition, the surrounding environment is quite calm making this village as one of the tourist destinations based on ecological, community custom and cultural values so it can make Taro Village has the potential to be developed into an eco-spiritual destination. The research aims to identify the potentials and weaknesses that exist in Taro Village, as well as the opportunities and external obstacles faced by Taro Village. The method used in this research is qualitative approach by using a SWOT analysis. The results show that Taro Village can be developed into an eco-spiritual tourist by maximizing the strategy according to its potential and minimizing the weaknesses in Taro Village.